Evolution or Revolution: from Digital Twin to Metaverse a Critical Review - Elena LACATUS (Communications of International Proceedings, 2021)
In the last few months, we have witnessed the media explosion of the Metauniverse concept. The Digital Twin has been talked about for some time, in the process of digital transformation that is set to ensure the transition to and integration into Ind4.0 Naturally, an analysis is needed to establish the similarities and differences between the two digital phenomena, which justify the popularity of the Digital Twin in recent years and which underpin the hypotheses of a trans-dimensional virtual world - the Metauniverse. Seen as the future virtual environment of the internet, the Metauniverse is conceived in the real world, with which it interacts and with which it is constantly online; the Digital Twin is instead a symbiosis between the real object and its virtual image, connected in real time and interacting dynamically. Despite the fact that the two concepts seem to have many similarities, they are not identical. In order to determine the relationship between the Metauniverse and the Digital Twin we need to go beyond the definitions, looking at how each of them is configured and implemented, the impact they can have in changing the social paradigm and the consequences of the transformation, evolution or revolution they produce.
Keywords: Metauniverse; Digital Twin; Metaverse; Communications Management; Ethics